Mathematical sequence behind genetic codes - Nur Syafiqah Mohamad Aris (2019)
In a world where science and mathematics are ever-advancing and ever-growing, it is no surprise that great discoveries relating the mentioned to radically everything has been made over time. Among those many discoveries lie the complicated yet intriguing relationship between mathematics and nature. The purpose of this study is to look further into this discovery - through ﬁnding the mathematical aspect which in this case, is the mathematical sequence, to the genetic code; a whole form of sequence within the forms of living there is to the earth. Trials and errors have been applied on varying forms of sequences as a method to discover the direct relationship between these sequences and the genetic code. Here, the genetic code table used was not the canonical one. In addition to that, the table has been split into three different segments to allow more in-depth perspectives. . Then onwards, the results attained were analysed separately based on the respective segments. The success of this study could create many opportunities for the future development and study on the biosystems of different forms of living; including predicting, altering, or fabricating the codes to achieve new, varying results.